2017
DOI: 10.5543/tkda.2017.95554
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in the elderly

Abstract: Hypertension (HT) is a common problem in elderly persons (age >65 years), reaching a prevalence as high as 60 to 80%. Isolated systolic HT mostly occurs in older patients. Treatment of HT in all patients, independent of age, consists of lifestyle modifications and antihypertensive therapy. Randomized trials have provided clear evidence of benefit from treating HT in elderly patients, including those over the age of 80 years. Drug therapy should be started in elderly hypertensive patients if lifestyle changes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This finding is reasonable because advanced age is known to be related to higher neurological disease incidence. It is well-described in the literature that HT is a common problem in geriatric patients with a prevalence as high as 60 to 80% [ 23 ]. In a study by Salvi et al, it was reported that the most common diagnoses in elderly patients were atrial fibrillation, congestive heart failure, pneumonia, and stroke [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is reasonable because advanced age is known to be related to higher neurological disease incidence. It is well-described in the literature that HT is a common problem in geriatric patients with a prevalence as high as 60 to 80% [ 23 ]. In a study by Salvi et al, it was reported that the most common diagnoses in elderly patients were atrial fibrillation, congestive heart failure, pneumonia, and stroke [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies on moths in the Black Sea region are as follows. [3][4][5][6][7][8][9][10][11][12] According to 13 687 species of Geometridae are distributed in Türkiye. Eupithecia nemrutica (Seven, Mironov & Akın, 2019) as a new species reported from the Adıyaman province of Türkiye.…”
Section: Introductionmentioning
confidence: 99%